A bi-DOPO type of flame retardancy epoxy prepolymer: Synthesis, properties and flame-retardant mechanism. (August 2021) - Liu, Dongyue; Ji, Pengfei; Zhang, Tianlong; Lv, Jipeng; Cui, Yihua
Highlights: l The intrinsic flame-retardant epoxy prepolymer ( d -FREP) was directly synthesized from bisphenol A and bi-DOPO compound. l The cured d -FREP achieved smoke suppression and fire safety. l The flame inhibition was here the main mode of flame retardancy (42% reduction), charring (reduction in fuel released) the minor one (17% reduction). l The cured d -FREP possessed high glass transition temperature and tensile strength. Abstract: A bi-DOPO type of prepolymer for flame retardancy epoxy resins with intrinsically flame-retardant was successfully synthesized by reacting of 6, 6′-((6, 6′-dihydroxy-[1, 1′-biphenyl]-3, 3′-diyl) bis (propane-3, 1-diyl)) bis(dibenzo[c, e][1, 2] oxaphosphinine 6-oxide) (DOBP) with bisphenol A. The characterization of the cured epoxy resins, such as cone calorimeter, TGA/infrared, Raman and SEM indicated that DOBP with double 9, 10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide (DOPO) structure endowed the epoxy resins with excellent flame retardancy, including limiting oxygen index of 40.0%, V-0 rating in UL-94, remarkable smoke suppression and flame inhibition. The quenching effect of gaseous phase and charring effect of condensed phase of phosphaphenanthrene groups in prepolymer together contributed to the improvement on the flame retardant performance of the epoxy resins. In addition, due to the rigid structure of DOBP molecules, the cured d -FREP possessed high glass transition temperature of up to 192.9°C, and the tensile modulus of which was increased about 55% compared with the neat epoxy resins.